Product Contagion: Changing Consumer Evaluations through Physical Contact with “Disgusting” Products - Morales, Andrea C.; Fitzsimons, Gavan J. (Journal of Marketing Research, 2007)
This research demonstrates the strong influence of disgust in a consumer context. Specifically, it shows how consumer evaluations may change in response to physical contact with products that elicit only moderate levels of disgust. Using evidence from six studies, the authors develop a theory of product contagion, in which disgusting products are believed to transfer offensive properties through physical contact to other products they touch, thus influencing evaluations.